Vitamin content of athletes of various sports: assessment of the diet and blood serum level - A. V. Pogozheva; E. E. Keshabyants; N. A. Beketova; V. M. Кodentsova; O. A. Vrzhesinskaya; O. V. Kosheleva (National Electronic Information Consortium (NEICON), 2020)
Objective: to study the vitamins level in athletes of various sports. Materials and methods: during the training process, 400 athletes of various sports and specializations were examined: martial artists, game sport athletes, cyclic, complex coordination sports. We assessed the dietery intake of vitamins A, C, B1, B2 and PP and the blood serum level of vitamins A, E, C, B2 and beta-carotene. Results: The assessement the dietary intake of vitamins in relation to the energy value revealed insufficient intake of vitamins B1, B2 and PP in vast majority of the athletes. Only 15.2% of athlets demonstrated adequate level of all vitamins. Most frequently we found a reduced blood serum riboflavin concentration. Conclusions: An increase of B vitamins dietary intake by athletes through a high level of dietary vitamin supplements.